2022
DOI: 10.1103/physrevresearch.4.043195
|View full text |Cite
|
Sign up to set email alerts
|

Functional observability and subspace reconstruction in nonlinear systems

Abstract: Time-series analysis is fundamental for modeling and predicting dynamical behaviors from timeordered data, with applications in many disciplines such as physics, biology, finance, and engineering. Measured time-series data, however, are often low dimensional or even univariate, thus requiring embedding methods to reconstruct the original system's state space. The observability of a system establishes fundamental conditions under which such reconstruction is possible. However, complete observability is too rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…We want to employ algebraic methods to obtain a functional observer. For the high gain observer (10) we need the map 𝛼 of the observability canonical form (6). The coordinates 𝑧 1 , … , 𝑧 𝑁 of the canonical form are defined by Lie derivatives of order 0, … , 𝑁 − 1, see (4) and (5).…”
Section: Observer Design For Polynomial Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…We want to employ algebraic methods to obtain a functional observer. For the high gain observer (10) we need the map 𝛼 of the observability canonical form (6). The coordinates 𝑧 1 , … , 𝑧 𝑁 of the canonical form are defined by Lie derivatives of order 0, … , 𝑁 − 1, see (4) and (5).…”
Section: Observer Design For Polynomial Systemsmentioning
confidence: 99%
“…This work was inspired by the literature [6], where the functional observability was investigated for the Lorenz system, among others, and a functional observer was designed. The observation was based on a partial inversion of the observability map, where the functional was expressed in terms of the output and its time derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study reported a tremendous increase in the computation time of the greedy method and the SDP relaxation method for a power grid system of such a size [66]. There are likely to be computational issues when the optimization objective is further extended to the observability for the nonlinear state space models [44,68,69], the error covariance of the Kalman filter [70][71][72][73][74], and the H 2 norm of an LTI system, which can be reduced through balanced truncation [75][76][77]. Accordingly, the main interest in this study is the applicability of the Gramian-based methods for the larger scale system constructed by the data-driven modeling methods.…”
Section: Introductionmentioning
confidence: 99%